In Vivo Electroporation-Mediated, Intrahepatic Alpha1 Antitrypsin Gene Transfer Reduces Pulmonary Emphysema in Pallid Mice - Marco A. Sutter; Tiziana P. Cremona; Izabela Nita; Eleonora Cavarra; Giuseppe Lungarella; Eli C. Lewis; Johannes C. Schittny; Thomas Geiser; Amiq Gazdhar (Pharmaceutics, 2020)
Rationale: Mutation in the alpha1 antitrypsin (AAT) gene leads to low circulating levels of AAT, which is associated with several disease processes including pulmonary emphysema. The standard of care relies on substitution with plasma-purified AAT. We studied a novel approach to obtain sustained therapeutic levels of circulating AAT using nonviral in vivo electroporation-mediated gene transfer to the liver. Methods: In vivo intrahepatic electroporation-mediated human AAT gene transfer was performed in C57 Bl/6J mice carrying a genetic deficiency of murine AAT (pallid mice) and suffering from pulmonary emphysema. The animals were evaluated for lung function using flexiVent and detailed stereological assessments. Lung neutrophilic burden was assessed. Results: Pallid mice showed morphologically detectable pulmonary emphysema. Thirty days after in vivo electroporation-mediated gene transfer directly aimed at the liver, circulating human AAT was elevated and lung function was significantly improved compared to non-treated pallid mice. Stereological analysis revealed a reduction in pulmonary emphysema. Conclusion: Our data indicate that in vivo intrahepatic electroporation-mediated gene transfer of AAT is a safe and efficient procedure resulting in reduction of pulmonary emphysema in pallid mice.